Tritium planigraphy: From the accessible surface to the spatial structure of a protein - Bogacheva, Elena N. (The National Academy of Sciences, 1998)
The method of tritium planigraphy, which provides comprehensive information on the accessible surface of macromolecules, allows an attempt at reconstructing the three-dimensional structure of a protein from the experimental data on residue accessibility for labeling. The semiempirical algorithm proposed for globular proteins involves (i) predicting theoretically the secondary structure elements (SSEs), (ii) experimentally determining the residue-accessibility profile by bombarding the whole protein with a beam of hot tritium atoms, (iii) generating the residue-accessibility profiles for isolated SSEs by computer simulation, (iv) locating the contacts between SSEs by collating the experimental and simulated accessibility profiles, and (v) assembling the SSEs into a compact model via these contact regions in accordance with certain rules. For sperm whale myoglobin, carp and pike parvalbumins, the λ cro repressor, and hen egg lysozyme, this algorithm yields the most realistic models when SSEs are assembled sequentially from the amino to the carboxyl end of the protein chain.